Trophic ecology of an abundant predator and its relationship with fisheries - Barnett, Adam (2013)
Trophic studies are key components in animal ecology and fisheries research. Although stomach samples are often obtained from fisheries, diet studies that consider the influence of fisheries on dietary results are still lacking. Here, the diet of the draughtboard shark Cephaloscyllium laticeps, an abundant mesopredator in Tasmanian waters, was investigated. Stomach samples were obtained from gillnet and craypot fisheries sourced from 4 regions: central (100% gillnet), east coast (63% gillnet, 37% craypot), northwest (100% gillnet), and southwest Tasmania (100% craypot). Overall, C. laticeps consumed the same prey types in all regions, but the importance of some prey varied significantly between regions. Generalized linear models showed that region was the main factor affecting prey abundance in the diet. Fishing method had some influence on the abundance of some prey (crabs, octopus, and other molluscs (gastropods and bivalves)), but the effect of fishing method on pot-related species such as Jasus edwardsii (lobster) and octopus was not as prevalent as expected. The common occurrence of C. laticeps as a bycatch species and its high consumption of targeted fishery species (lobsters and octopus) indicates that C. laticeps has a strong interaction with the fisheries. Therefore, the relationship between these fishery species and C. laticeps should be considered in food web studies in Tasmanian waters.